Development and power consumption analysis of low cost wireless sensor node for fire detection. (28th September 2020) - Sharma, Shivani; ,; Chand, Kailash; Sharma, Deepak; Guha, Paramita
Fire becomes a problem when it goes untamed and destroys in part or whole the ecological balance of the area. Thus arises a need to develop a system for early detection of fire with significant accuracy. In this work, a wireless sensor network has been developed for fire detection and its essential parameters, such as effective detection distance and power consumption have been monitored. The hardware developed for this system comprises of the components as a controller board and a transceiver. Without the inclusion of energy saving algorithm the system has shown a considerable lifetime and effective detection distance.